Interpreting The Uniqueness of Jepara Javanese Language As Cultural Identity in order to Preserve Local Wisdom (A Study of Dialectology) - Aliva Rosdiana; Olyvia Revalita Candraloka (ELITE JOURNAL, 2023)
Interpreting Jepara Javanese dialect aims at preserving local language inherited by Javanese society in language conversation as a study of dialectology. The uniqueness of Jepara Javanese language has differently varying social context from other Javanese language outside Jepara and specific functions of language to convey cultural identity that cannot be found outside Jepara due to distinctive Javanese language used. It is a descriptive qualitative research with phenomenological thinking strategies to reveal various meanings reflected from verbal of the people in Jepara which contain local wisdom in it. People, verbally, produce local languages with particular “ngoko” dialects to communicate each other. The dialect gloss of “ngoko” used are such as nderok, gene, watake, luru, mberuh, makno, etc. Finally, Jepara Javanese language becomes cultural identity for speakers of a given language with their own characteristics to preserve local language wisdom through social behavior. Keywords: dialect; dialectology; local language wisdom; Jepara Javanese language; cultural identity